Pelatihan Fitrah Based Education Bagi Orang Tua Dalam Menumbuhkan Potensi Anak Secara Holistik di Desa Mendalo Indah - Ady Muh. Zainul Mustofa; Salman Jufri; Salman Hasani; Rofiazka Fahmi Huda; Muhammad Sobri (Politeknik Piksi Ganesha Indonesia, 2026)
Parenting patterns play a crucial role in determining the direction of a child's development, especially during the golden age. However, many parents in rural areas still lack a deep understanding of nature-based parenting. This community service activity aims to provide Fitrah Based Education (FBE) training to parents in Mendalo Indah Village, Muaro Jambi Regency. The implementation method involves a participatory approach through socialization, training, hands-on practice, the use of digital technology, and ongoing mentoring. The results of the community service show a significant increase in parents' understanding of their children's natural aspects, practical parenting skills, and the formation of a PKK-based learning community. The discussion relates the findings to the literature on holistic education, parenting, and FBE theory. This activity contributes to strengthening family capacity in supporting children's holistic growth and development, which is relevant to the SDGs (Quality Education, Gender Equality, and Good Health).